Моделирование процессов умягчения воды на катионитовых фильтрах - Обертас, И.А.; Олейник, А.Я. (Видавничий дім "Академперіодика" НАН України, 2007)
We present a mathematical model of the water softening (removal of excessive hardness) using cationite filters by ionic exchange of cation Na, which is contained in the cationite composition, by cation Ca or Mg which is contained in contaminated water. Some particular models of softening are developed.